Pengaruh Model Pembelajaran Talking Stick Terintegrasi Saintifik Berbantuan Media Charta Terhadap Hasil Belajar Kognitif Peserta Didik Kelas VIII SMP Negeri 16 Halmahera Selatan - Zakir Aloahyt; Dharmawaty M. Taher; Abdu Mas'ud (JURNAL BIOEDUKASI, 2022)
The scientifically integrated talking stick learning model assisted by charta media is a learning stage following the steps of the talking stick learning model with charta-assisted media to improve the ability of students' cognitive learning outcomes. This study aims to determine the effect of the scientifically integrated talking stick learning model assisted by chart media on students' cognitive learning outcomes. This research is a quasi-experimental research (Quasy Experiment). The sample of this study consisted of two classes, namely class VIII-1 as the experimental class and VIII-2 as the control class with a total of 35 students. The instrument used is a test to measure cognitive learning outcomes. Data analysis used the SPSS-assisted normality and homogeneity test, while the hypothesis test used the Anacova test. The results showed that the talking stick learning model with chart media had an effect on learning outcomes with a significant level of 0.05 0.001.